Extracellular signal-regulated kinase-dependent phosphorylation of histone H3 serine 10 is involved in the pathogenesis of traumatic brain injury - Zhang, Yu; Yang, Xin; Hou, Xinran; Zhou, Wen; Bi, Changlong; Yang, Zhuanyi; Lu, Sining; Ding, Zijin; Ding, Zhuofeng; Zou, Yu; Guo, Qulian; Schäfer, Michael K. E.; et al. (Frontiers in Molecular Neuroscience, 2022)
Traumatic brain injury (TBI) induces a series of epigenetic changes in brain tissue, among which histone modifications are associated with the deterioration of TBI. In this study, we explored the role of histone H3 modifications in a weight-drop model of TBI in rats. Screening for various histone modifications, immunoblot analyses revealed that the phosphorylation of histone H3 serine 10 (p-H3S10) was significantly upregulated after TBI in the brain tissue surrounding the injury site. A similar posttraumatic regulation was observed for phosphorylated extracellular signal-regulated kinase (p-ERK), which is known to phosphorylate H3S10. In support of the hypothesis that ERK-mediated phosphorylation of H3S10 contributes to TBI pathogenesis, double immunofluorescence staining of brain sections showed high levels and colocalization of p-H3S10 and p-ERK predominantly in neurons surrounding the injury site. To test the hypothesis that inhibition of ERK-H3S10 signaling ameliorates TBI pathogenesis, the mitogen-activated protein kinase–extracellular signal-regulated kinase kinase (MEK) 1/2 inhibitor U0126, which inhibits ERK phosphorylation, was administered into the right lateral ventricle of TBI male and female rats via intracerebroventricular cannulation for 7 days post trauma. U0126 administration indeed prevented H3S10 phosphorylation and improved motor function recovery and cognitive function compared to vehicle treatment. In agreement with our findings in the rat model of TBI, immunoblot and double immunofluorescence analyses of brain tissue specimens from patients with TBI demonstrated high levels and colocalization of p-H3S10 and p-ERK as compared to control specimens from non-injured individuals. In conclusion, our findings indicate that phosphorylation-dependent activation of ERK-H3S10 signaling participates in the pathogenesis of TBI and can be targeted by pharmacological approaches.